1152 "A Hypoxic Dilemma"- Compliance with Oxygen Prescriptions on The Acute Surgical Take. (12th October 2021) - Shaladi, A; Jesuthasan, J; Martin, G; Allu, J; Shah, A
Abstract: Aim: British Thoracic Society Guidelines state that all patients admitted to hospital should have oxygen targets prescribed to promptly start oxygen therapy should clinical deterioration occur. We aimed to assess oxygen prescribing compliance for new surgical patients. Method: We assessed prescription of oxygen in patients admitted on the surgical take, once weekly for 8 weeks looking at target values, route of administration, frequency and appropriate signing and dating. A re-audit was performed after presenting the initial results at a department meeting. Results: 61 patients were included. Out of 61, 8 patients had COPD. Only 9 patients had adequate oxygen prescriptions with all the criteria completed. After re-audit, 50 surgical take patients' drug charts were reviewed. 42 out of 50 patients had correctly completed oxygen prescriptions. Conclusions: Correct oxygen administration in high-risk patients is vital in their management, particularly during clinical deterioration. A discernible improvement in prescriptions was noted in this study.